The Meaning of the Local Tradition of Makan Beseprah/Berkerobok: A Symbolic Interactionism Study of the Kutai People in East Kalimantan - Ida Suryani Wijaya; Rega Armella; Iffah Khairunnikmah; Didek Yustika (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to explore the meaning of the beseprah (bekerobok) communal eating tradition among the Kutai people in East Kalimantan, who continue to preserve local customs amid the forces of modernization. The research employs a qualitative method with an ethnographic approach. The researcher was directly involved in the community through participant observation and in-depth interviews to understand the values and symbols embedded in this cultural practice. The findings reveal that the beseprah tradition holds significant symbolic meaning in fostering togetherness, strengthening social bonds, and expressing gratitude. The shared meals reflect local wisdom and serve as a space to introduce traditional Kutai cuisine. This tradition also plays a social role by reducing class distinctions. However, its implementation faces challenges, such as limited institutional support and shifting meanings due to modern influences. Nonetheless, through cooperation among stakeholders, the core values of beseprah can still be preserved. This study contributes to academic discussions in cultural anthropology and symbolic interactionism, particularly in understanding how local traditions are maintained and reinterpreted in the modern era. The findings reinforce the importance of preserving local culture as part of national identity and as a form of resistance to global cultural homogenization. Using a symbolic interactionist lens, the research provides in-depth insights into how social interaction and symbols construct shared meanings in local traditions. It also opens a dialogue on the role of community in sustaining culture as a source of long-term social strength.